Recognition of Relevant ORP, pH, and DO Bending Points in Ammonia Removal from Drinking Water through Online BAF System - Hassimi Abu Hasan; Siti Rozaimah Sheikh Abdullah; Siti Kartom Kamarudin; Noorhisham Tan Kofli (International Journal of Chemical Engineering)
This study was undertaken to identify the relevant bending points in ORP, pH, and DO profiles in ammonia removal through online monitoring. A novelty BAF system as newl application for drinking water treatment that equipped with ORP, pH, DO NH4 + and NO3 − sensors was used. Two types of polluted drinking water strength (low and high strength) with various NH4 + concentrations and aeration flow were treated at a fixed-time reaction of 24 h. Experiments were conducted at four track studies (TS) of TS1 (NH4 += 50 mg/L, aeration = 0.3 L/min), TS2 (NH4 + = 100 mg/L, aeration = 2.0 L/min), TS3 (NH4 += 100 mg/L, no aeration) and TS4 (NH4 += 10 mg/L, aeration = 0.1 L/min). The results showed that the removal of NH4 + was more than 95% for TS1, TS2, and TS4. From the online monitoring performances, DO elbow and ammonia valley appeared in ORP and pH profiles, respectively. Similarly, new positive plateaus were observed in DO, indicating that the nitrifiers stopped to consume the DO after NH4 + was completely removed. Hence, based on the bending points, the aeration system is possible to be automatically stopped just after DO elbow and ammonia valley appears in order to save the energy consumption and to shorten the time demands for the drinking water treatment process.